Bullying Victimization, Interpersonal Difficulties, And Loneliness in School Children - Maryam Haneef; Dr. Shammem Akhtar (Social Science Review Archives, 2025)
This study explored the relationship between bullying victimization, interpersonal difficulties, and loneliness among school children. A cross-sectional research design was used, and a stratified random sample of 300 students aged 13–18 years was selected. Standardized instruments, including the Bullying Victimization Scale (Amjad & Saleem, 2014), the Interpersonal Difficulties Scale (Saleem, et al., 2014), and the UCLA Loneliness Scale Version 3 (Russell, 1996), were administered. The findings revealed significant positive correlations between bullying victimization, interpersonal difficulties, and loneliness. Regression analysis indicated that bullying victimization significantly predicted both loneliness and interpersonal difficulties. Gender differences were also observed, with male students reporting higher victimization. The results highlight the detrimental role of bullying on children’s social and emotional development and underscore the need for targeted school-based interventions.